Comparing toxicity of galbanic acid, auraptene and umbelliprenin on adult T-cell leukaemia-lymphoma in normoxia and hypoxia: Toxicity of GBA, AUR and UMB on ATL in normoxia and hypoxia - Goudarzi, Sajad; Rassouli, Fatemeh B.; Kahrizi, Danial; Paryan Shirkhani; Mahdifar, Maryam; Mehrdad Iranshahi; Houshang Rafatpanah; Keramati, Mohammad Reza; Hossein Ayatollahi (Cellular and Molecular Biology, 2022)
Natural coumarins are valuable agents that induce anticancer effects and/or enhance sensitivity to therapeutic modalities. Galbanic acid (GBA), auraptene (AUR) and umbelliprenin (UMB) are coumarins derived from Ferula species with various pharmaceutical activities. The aim of the current research was to compare toxic effects of GBA, AUR, and UMB on human lymphoma cells in normoxia and hypoxia. In this regard, GBA and AUR were extracted from the roots of F. szowitsiana and UMB was derived from the roots of F. persica, all by thin-layer chromatography. MT-2 cells were treated with each agent for 3 consequent periods, while exposed to different O2 contents (21% and 2%). By the end of each treatment, the viability of MT-2 cells was determined by resazurin dye-based colorimetric assay. Obtained results revealed that low doses of GBA (10 and 20 µM) induced significant (p < 0.0001) toxic effects in hypoxia. However, similar toxicity was observed when cells were treated with 40 µM AUR in normoxia and hypoxia. Notably, UMB was the only coumarin that exerted cytotoxic effects in all time points (48, 72 and 96 h) in normoxia and hypoxia, although its concentration was highest (80 µM). In conclusion, this is the first report indicating GBA was the most toxic coumarin against ATL cells in hypoxia, AUR induced similar effects in normoxia and hypoxia, and low toxicity of UMB was stable during the time and different O2 contents. Future studies on other ATL cell lines are recommended to better evaluate the toxic effects of GBA, AUR and UMB in vitro.